1990
DOI: 10.1152/ajpheart.1990.258.4.h1049
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial modulation of norepinephrine-induced constriction of rat aorta at normal and high CO2 tensions

Abstract: Endothelial modulation of norepinephrine (NE)-induced constriction of the isolated rat aorta was studied at normal (PCO2, 41 +/- 0 mmHg) and high CO2 tensions (PCO2, 91 +/- 1 mmHg). In preparations with intact endothelium, increased CO2 tension resulted in rightward shift of the NE dose-response curve with attenuation of maximal contraction. This effect of CO2 was not modified by indomethacin. Treatment with hemoglobin or rubbing of the endothelium meant that increased CO2 tension still resulted in rightward s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 0 publications
2
21
1
Order By: Relevance
“…No effect of the NOS inhibitors was observed on basal coronary flow, excluding the role of NO in the regulation of basal coronary vascular tone. This observation conflicts with in vitro findings in guinea pig Langendorff heart preparations, in which NOS inhibition reduced basal coronary vascular flow (21)(22)(23).…”
Section: Respiratory Acidosiscontrasting
confidence: 89%
See 1 more Smart Citation
“…No effect of the NOS inhibitors was observed on basal coronary flow, excluding the role of NO in the regulation of basal coronary vascular tone. This observation conflicts with in vitro findings in guinea pig Langendorff heart preparations, in which NOS inhibition reduced basal coronary vascular flow (21)(22)(23).…”
Section: Respiratory Acidosiscontrasting
confidence: 89%
“…NO was proposed as a mediator of hypercapnia-evoked coronary vasodilation in the in situ dog heart (20) and findings in isolated aortic strips suggest that vasorelaxation in this artery in response to CO 2 may be partially mediated by NO (21). A number of publications have implicated NO in the vasodilatory response of the cerebral vasculature to hypercapnia (22), although more recent evidence suggests that the role of NO may be "permissive" rather than "causative" in this vascular bed (23).…”
Section: Respiratory Acidosismentioning
confidence: 99%
“…Ten and 20 mmol/L NH,C1 increased resting vascular tone slightly (3,5,10, and 20 mmol/L: not determined, 3±2%, 9±3%, and 13±4% of KC1 contraction) and potentiated norepinephrine contraction (Fig 1). In contrast, 3 and 5 mmol/L NH,C1 did not significantly change resting vascular tone and norepinephrine contraction.…”
Section: Experiments 1: Effect Of Changes In Ph On Acetylcholine Relamentioning
confidence: 87%
“…High CO 2 tension suppressed norepinephrine-induced contraction in rat aorta, possibly with endothelial modulation. 5 Our recent study 8 suggested that acetylcholine relaxation was modified by altered activity of Na + -H + antiport. Thus, NFLjCl-induced impairment of acetylcholine relaxation may be mediated through endothelial function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation